Dogface Soldiers. Die Frontsoldaten der US-Infanterie und der Krieg gegen Hitlers Wehrmacht im Mittelmeerraum und Nordwesteuropa - Büchl, Marco (2016)
Dogface Soldiers is an interdisciplinary and image centered cultural history of the Army of the United States' infantry riflemen in the Mediterranean- and European Theaters of Operations of World War II. Its methods transcend the boundaries of conventional historiography and make use of Clifford Geertz's anthropological method of thick description as well as military used comprehensive analysis methods.